Nuclear Factor Kappa-B Mediates Selective Induction of Neuronal Nitric Oxide Synthase in Astrocytes During Low-Level Inflammatory Stimulation with MPTP - Carbone, David L. (2008)
Recent advances in understanding the progression of Parkinson’s disease (PD) implicate perturbations in astrocyte function and induction of constitutively expressed neuronal nitric oxide synthase (NOS1) in both human PD and in the MPTP model of the disease. Transcriptional regulation of NOS1 is complex but recent data suggest that nuclear factor kappa B (NF-κB) is an important transcription factor involved in inducible expression of the gene. The data presented here demonstrate that mild activation of primary astrocytes with low or ‘sub-optimal’ concentrations of MPTP (1 µM) and the inflammatory cytokines tumor necrosis factor alpha (10 pg/ml) and interferon gamma (1 ng/ml) results in selective induction of Nos1 mRNA and protein, increased production of nitric oxide (NO), and a significant elevation in global protein nitration. This mild inflammatory stimulus also resulted in activation and recruitment of p65 to a putative NF-κB response element located in the Nos1 promoter region flanking exon 1. A role for NF-κB in MPTP-dependent induction of NOS1 was confirmed through overexpression of a mutant IκBα super repressor of NF-κB that prevented induction of NOS1. The data presented here thus demonstrate a role for NF-κB in selective induction of NOS1 during early inflammatory activation of astrocytes stimulated by low-dose MPTP and inflammatory cytokines.